(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Armed conflicts represent one of the most common causes that lead to people going missing. As soon as the intensity of hostilities goes up in a country, the voices of families seeking information about the fate of their children rise. At that point, the state has a duty to offer the needed support and assistance to the affected families, either by facilitating the practical procedures that aim to query about the missing persons and restore family links or by enacting appropriate legislation to guarantee the rights of missing persons and their families and decrease the likelihood of people going missing. In order to adopt such legislation, states could rely on the model legislative provisions prepared by the ICRC with a view to providing states with a road map for dealing with similar situations.